Heat transfer enhancement of air-cooled heat sink channel using a piezoelectric synthetic jet array. (November 2019) - Yeom, Taiho; Huang, Longzhong; Zhang, Min; Simon, Terrence; Cui, Tianhong
Highlights: Heat transfer of heat sink channel can be enhanced with synthetic jet arrays. Square orifice showed the best cooling performance among various orifice shapes. Numerical Studies showed good agreements with experimental results. Synthetic jet arrays can enhance heat transfer at a fin tip by up to 413%. Abstract: In the last decade, active devices, such as synthetic jets have been intensively studied for electronics cooling. The present study experimentally and computationally investigates heat transfer performance of synthetic jet arrays used in heat sink channels. The heat sink of the present study consists of multiple flow channels that are parallel to one another. The channel walls behave like fins in that their tops are exposed to the flow. The jets are designed to impinge on the tops and sides of those fins to augment heat transfer. The current study employs a single channel of the heat sink to investigate heat transfer augmentation performance by the jets. The oscillating diaphragms that create the jets are driven by a piezo-bow operating at its second resonant vibrational mode to generate a large oscillatory displacement at a high working frequency. The frequency for this study is 1240 Hz and the measured displacement of the jet-driving diaphragm is 0.5 mm. The corresponding peak velocity of each jet is around 45 m/s and the total power consumption is 1.6 W when operating with 20 jets. Heat transfer experiments using jet arrays of different jet orifice configurations are conducted in a single narrow channel that represents one of the channels of a multi-channel heat sink. With a through-flow velocity of 14.7 m/s driven by a centrifugal fan, the synthetic jet arrays with square orifices achieve 9.3% enhancement on heat transfer coefficient averaged over the entire fin (channel wall) surface, compared to the value for a case with through-flow only. When the channel through-flow velocity decreases to 8 m/s spatially-averaged heat transfer enhancement by the jets is 21.7%; again, averaged over the entire fin (channel wall) surface. In a computational study, the jet diaphragm movement is realized with a dynamic mesh available within the commercial software package ANSYS Fluent. Computed surface-average Nusselt numbers show good agreement with the experimental data, differing by no more than 10%. The numerical study was performed to quantify the effects of system parameters, such as the jet and channel flow rates and orifice-to-fin-surface distance, on heat transfer performance over different sections of the channel (fin) wall. According to the results of the numerical study, the synthetic jets have a strong cooling effect on the channel wall tip region, the nearest surface to the jet orifice, and a weaker effect on the channel side surfaces. It is found that the synthetic jet can enhance locally-averaged heat transfer coefficients at the fin tip by up to 413%, compared to a case with cooling by channel through-flow only.